Nearbyou: a crowdsourced app for finding the best places for peace and quiet - Muhammad Zufiqqar Bin Jamal (Nanyang Technological University, 2022)
Taking a break from hectic work schedules, loud friend groups, and being away from a loud or chaotic in your environment is essential to health. It helps relieve stress, restores mental wellness, and improves cognition. However, it may be challenging to find a place to relax and meditate especially in urbanized and urbanizing areas.